Reasons Behind the Migration of Highly Qualified Employees from Turkiye: The Case of Software Developers and Engineers - Mustafa Şeref Akın; Ebubekir Karadaş (Journal of Economy Culture and Society)
The emigration of highly skilled software developers and engineers from Turkey has gained momentum, leading to a shortage of technical staff in technology companies, particularly startups. In order to understand their motivations for migrating, interviews were conducted with software developers and engineers. The findings reveal that highly skilled individuals perceive their labor as undervalued in Turkey, both economically and in terms of social status. The international nature of the software industry makes it relatively easy for them to migrate to other countries or work for foreign companies remotely. They express that companies in their destination countries respect their work, private lives, and individuality. To address this issue, Turkish companies can consider measures such as assisting key employees in purchasing houses and cars, as well as supporting their families’ education and healthcare expenses, to ensure long-term loyalty. Furthermore, it is suggested that salaries for software developers should be adjusted to be more comparable to those abroad in terms of purchasing power. Failure to provide sufficient incentives may result in software exports falling short of expectations amidst this wave of migration.